2017
DOI: 10.1177/0093854817719915
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Changes in Dynamic Risk Factors and the Predictive Validity of Risk Assessments Among Youth Offenders

Abstract: The Youth Level of Service/Case Management Inventory (YLS/CMI) is a widely used risk assessment tool for youth offenders. It is intended to be administered regularly to capture changes in criminogenic needs and thus inform case management during a youth’s sentence. However, there is a dearth of research examining whether updated assessments are more predictive of recidivism than initial assessments. We examined whether including dynamic risk factors increased the predictive validity of the YLS/CMI and whether … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 52 publications
0
29
0
Order By: Relevance
“…In one study, youth on probation showed mean-level decreases in YLS/CMI scores over time, thus providing evidence for the YLS/CMI's internal sensitivity (Clarke, Peterson-Badali, & Skilling, 2016). Also, decreases in total scores and some subscales predicted decreased risk of reoffending, thus providing support for the YLS/CMI's external sensitivity.…”
Section: Sensitivity To Changementioning
confidence: 98%
“…In one study, youth on probation showed mean-level decreases in YLS/CMI scores over time, thus providing evidence for the YLS/CMI's internal sensitivity (Clarke, Peterson-Badali, & Skilling, 2016). Also, decreases in total scores and some subscales predicted decreased risk of reoffending, thus providing support for the YLS/CMI's external sensitivity.…”
Section: Sensitivity To Changementioning
confidence: 98%
“…Similarly, studies using YLS/CMI also found evidence for the utility of change scores. Using a sample of 200 Canadian youth offenders, Clarke, Peterson-Badali, and Skilling (2017) found that the inclusion of changes in dynamic risk scores improved predictive accuracy.…”
Section: Types Of Transition In Risk Profilesmentioning
confidence: 99%
“…Research on the YLS/CMI is even scarcer. Even though some studies have examined changes in YLS/CMI risk total scores (Clarke, Peterson-Badali, & Skilling, 2017;, we are not aware of any research that has examined changes in YLS/CMI strengths, let alone how such change relates to reoffending. However, unless there is evidence that protective factors causally relate to reoffending, it cannot be assumed that targeting those factors in treatment will reduce reoffending (Monahan & Skeem, 2014).…”
Section: Putatively Causal Factorsmentioning
confidence: 99%